Solidification and stabilization of harmful elements in antimony tailings and synergistic utilization of multiple solid wastes. (October 2022) - Wu, Fenghui; Liu, Xinxin; Qu, Guangfei; Ning, Ping; Jin, Caiyue; Cui, Qingyuan; Ren, Yuanchuan; He, Minjie; Yang, Yuyi; Li, Junyan
Abstract: The massive generation and accumulation of tailings potentially lead to environmental pollution. Antimony tailings (AT) have higher environmental risks than other types of tailings and thus require special attention. Hence, this article used a variety of industrial solid wastes to solidify and stabilize the harmful components in AT. The solidified bodies prepared by adding different ratios of AT were cured under standard and natural curing conditions, and a series of performance tests and leaching toxicity analysis were performed. The results show that the solidified bodies containing 1000 g AT demonstrates excellent mechanical properties after standard curing for 28 d, with a compressive strength of 15 MPa and flexural strength of about 2.5 MPa. The solidified bodies have a water absorption rate of around 27%, softening coefficient of about 0.7, dry density of 900 kg/m 3 and wet density of 1100 kg/m 3, which meet waterproof and lightweight requirements. In addition, according to leaching toxicity analysis, the solidified bodies meet environmental standards. The bonding effect of needle-shaped ettringite and the encapsulation and filling effect of gelling substance are beneficial to the solidification and stabilization of AT. This article provides theoretical basis and research ideas for AT treatment and disposal.